Production of lactic acid by immobilized lactic acid bacteria in chitosan-coated alginate beads - 363116 Chew, Frederic Kok Jin; Zainoha Zakaria, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007